A Study on the Conceptual Framework for Appreciative Character Development Through Music Appreciation Learning - Putra, Agung Dwi; Budimansyah, Dasim; Milyartini, Rita; Nurdin, Encep Syarief (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study proposes a conceptual framework of appreciative character based on music appreciation learning, placing appreciative character as the main outcome of the learning process. This character is believed to foster critical awareness and positive attitudes towards beauty, diversity, and differences in social life. This study uses a descriptive-conceptual literature review to construct the proposed framework by synthesizing theories on intolerance, character education, virtue ethics, aesthetics, and music appreciation learning. The resulting conceptual framework offers a new perspective in responding to contemporary challenges in music education by expanding its epistemological foundation to include moral (character) and social dimensions. Within this framework, music appreciation learning is understood as an effort to cultivate moral virtues through mesos habits that include attention, repetition, and recognition in the process of music appreciation; while intellectual virtues are developed through systematic engagement with musical knowledge, including music theory, history, counterpoint, harmony, orchestration, composition, and related academic fields.